The action of distemper virus on the nervous system of dogs: Literature review (Research, Society and Development, 2023)
Distemper is an infectious and systemic disease, caused by a virus from the Paramyxoviridae family, of the Morbilivirus genus, which mainly affects dogs. Its transmission can occur through direct and indirect contact, through food, aerosols or objects contaminated with secretions containing the virus. The disease commonly affects young and adult dogs, without a racial or sexual predilection. The virus can concomitantly affect the respiratory, gastrointestinal, cutaneous and neurological systems, causing variable clinical signs, frequently being observed: fever, conjunctival secretion, cough, abdominal pustules, purulent nasal secretion, bloody mucous diarrhea, which can leave sequelae and reduce the quality of life or even, in most cases, cause the death of animals. The neurological manifestation of the disease is considered the most serious and worrying, as the virus replicates in neurons and glial cells, which can cause necrosis in the gray matter and also demyelination in the white matter of the brain. There is still no specific treatmen against the distemper virus, only therapeutic protocols used for symptomatic and supportive treatment, and it is extremely important to carry out immunoprophylaxis measures for prevention. In view of the above, the present study aimed to carry out a bibliographical survey regarding distemper in dogs, emphasizing the action of the virus on the neurological system in the species.